1993
DOI: 10.1103/physrevb.48.4823
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure and physical properties of amorphous carbon and its hydrogenated analogs

Abstract: A semiempirical molecular-dynamic density-functional approach is used to perform a systematic investigation of the stability, structure, and properties of quenched pure and hydrogenated amorphous carbon dependent on the mass density and the hydrogen concentration. By comparing the total structure energies for supercell clusters of equal composition and atom number, we obtain the most stable a-C:H configurations characterized by optimal chemical bonding corresponding to certain mass densities and hydrogen conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…Depending on preparation conditions and hydrogen concentration a-C:H materials can vary from soft, low-density phases with polymer-like atomic structures to hard, diamond-like materials with a high content of C-C sp 3 bonds. Even though a-C:H films have important practical applications due to their diverse properties [20] there has been only a handful of theoretical studies of these systems [47][48][49][50]. Moreover, due to computational costs all these attempts have been restricted to small system sizes and rather unrealistic conditions and are therefore of limited practical use.…”
Section: From A-c To A-c:hmentioning
confidence: 98%
“…Depending on preparation conditions and hydrogen concentration a-C:H materials can vary from soft, low-density phases with polymer-like atomic structures to hard, diamond-like materials with a high content of C-C sp 3 bonds. Even though a-C:H films have important practical applications due to their diverse properties [20] there has been only a handful of theoretical studies of these systems [47][48][49][50]. Moreover, due to computational costs all these attempts have been restricted to small system sizes and rather unrealistic conditions and are therefore of limited practical use.…”
Section: From A-c To A-c:hmentioning
confidence: 98%
“…Later, total energy calculations by Frauenheim et al [4] found that the sp 2 sites formed much smaller clusters, and these tended to be olefinic chain-like groups rather than aromatic. Recently, it was found that the Raman spectrum gave direct information on the sp 2 configuration [5].…”
mentioning
confidence: 99%
“…Possible forms of a-C are represented by the ternary phase diagram of a-C growth in Fig. 15 [13,60]. …”
Section: Forms Of Amorphous Carbonmentioning
confidence: 99%